The Cologne Picture Naming Test for Language Mapping and Monitoring (CoNaT): An Open Set of 100 Black and White Object Drawings - Weiss Lucas, Carolin; Pieczewski, Julia; Kochs, Sophia; Nettekoven, Charlotte; Grefkes, Christian; Goldbrunner, Roland; Jonas, Kristina (Frontiers in Neurology, 2021)
Language assessment using a picture naming task crucially relies on the interpretation of the given verbal response by the rater. To avoid misinterpretations, a language-specific and linguistically controlled set of unambiguous, clearly identifiable and common object-word pairs is mandatory. We, here, set out to provide an open-source set of black and white object drawings, particularly suited for language mapping and monitoring, e.g., during awake brain tumour surgery or transcranial magnetic stimulation, in German language. A refined set of 100 black and white drawings was tested in two consecutive runs of randomized picture order and was analyzed in respect of correct, prompt and reliable object recognition and naming in a series of 132 healthy subjects between 18 and 84 years (median 25 years, 64% females) and a clinical pilot cohort of ten brain tumour patients (median age 47 years, 80% males). The influence of important word- and subject-related factors on task performance and reliability was investigated. Overall, across both healthy subjects and patients, excellent correct object naming rates (97% vs. 96%) as well as high reliability coefficients (Goodman-Kruskal’s gamma = 0.95 vs. 0.86) were found. However, the analysis of variance revealed a significant, overall negative effect of low word frequency (p<.05) and high age (p<.0001) on task performance whereas the effect of a low educational level was only evident for the subgroup of 72 or more years of age (p<.05). Moreover, a small learning effect was observed across the two runs of the test (p<0.001). In summary, this study provides an overall robust and reliable picture naming tool, optimized for the clinical use to map and monitor language functions in patients. However, individual familiarization before the clinical testing remains advisable, especially for subjects which are comparatively prone to spontaneous picture naming errors such as older subjects of low educational level and patient with clinically apparent word finding difficulties.